Self-repairing polyethylene fiber-reinforced-concrete with bacillus subtilis bacteria a review - G. Ghoneim, Amr; A. Hassan, Hilal; A. Aboul-Nour, Louay (International Journal of Engineering and Technology, 2020)
Fibers and bacterial additives in concrete have achieved significant success as a construction material. This paper presents the field of concrete self-repairing by introducing both Bacillus subtilis bacteria and polyethylene fiber as a dual-components. The main research goal is to reveal the principles of concrete self-repairing. At first, the research investigates the fiber-reinforced-concrete behavior, the concrete self-repairing process with the Bacillus subtilis bacteria for forming bacterial-concrete. And then, the study highlights the damage-repairing numerical simulation of fiber-reinforced-bacterial-concrete. The research shows the bacterial-concrete benefits to durability and mechanical properties besides to the polyethylene fiber assistance to enhance post-cracking tensile resistance and the pre-peak elastic modulus of concrete. The novelty of the fiber-reinforced-bacterial-concrete is the matrix combined improvement of both basic material properties and the post-cracking deflection capacity.Â Â